2022
DOI: 10.1021/acs.chemrev.2c00491
|View full text |Cite
|
Sign up to set email alerts
|

Life in Multi-Extreme Environments: Brines, Osmotic and Hydrostatic Pressure─A Physicochemical View

Abstract: Elucidating the details of the formation, stability, interactions, and reactivity of biomolecular systems under extreme environmental conditions, including high salt concentrations in brines and high osmotic and high hydrostatic pressures, is of fundamental biological, astrobiological, and biotechnological importance. Bacteria and archaea are able to survive in the deep ocean or subsurface of Earth, where pressures of up to 1 kbar are reached. The deep subsurface of Mars may host high concentrations of ions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 211 publications
0
43
0
Order By: Relevance
“…Canonical double-stranded DNA structures are usually very stable under pressure. ,, Polymeric B-DNA structures with melting temperatures, T m , beyond about 50 °C are usually stabilized against unfolding upon pressurization, i.e ., the helix-to-coil transition of DNA is accompanied by a positive overall volume change, Δ V , suggesting that a positive thermal/hydration volume contribution outweighs a negative void volume contribution to Δ V at high temperatures, leading to positive values of the Clapeyron transition slope, d T m /d p . ,,, The stability of helical nucleic acid structures was found to be quite high because they are rather densely packed and their conformation is largely controlled by hydrogen bonds and π–π-stacking interactions between aromatic rings, which are not significantly affected or even stabilized by high pressure. This high stability of B-DNAs is generally not observed in the case of RNAs, ribozymes, and noncanonical DNA/RNA structures, where bends, twists, and cavities are structural features, similar to proteins, and consequently pressure-induced changes can alter their biochemical activities. ,, The tRNA Phe showed small negative volume changes upon unfolding, the pressure-dependent structural changes being rather small, however, with a maximum of about 15% unpaired bases observed upon pressurization up to 10 kbar . Pioneered by Sugimoto, Chalikian, Macgregor, and their co-workers, it was found that noncanonical nucleic acid structure, including DNA hairpins (DNA-HPs), G-quadruplexes (G4Qs), and i-motifs, are pretty pressure-sensitive, and their pressure-sensitivity varies with their base sequence and the type and concentration of the counterions present in solution. …”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Canonical double-stranded DNA structures are usually very stable under pressure. ,, Polymeric B-DNA structures with melting temperatures, T m , beyond about 50 °C are usually stabilized against unfolding upon pressurization, i.e ., the helix-to-coil transition of DNA is accompanied by a positive overall volume change, Δ V , suggesting that a positive thermal/hydration volume contribution outweighs a negative void volume contribution to Δ V at high temperatures, leading to positive values of the Clapeyron transition slope, d T m /d p . ,,, The stability of helical nucleic acid structures was found to be quite high because they are rather densely packed and their conformation is largely controlled by hydrogen bonds and π–π-stacking interactions between aromatic rings, which are not significantly affected or even stabilized by high pressure. This high stability of B-DNAs is generally not observed in the case of RNAs, ribozymes, and noncanonical DNA/RNA structures, where bends, twists, and cavities are structural features, similar to proteins, and consequently pressure-induced changes can alter their biochemical activities. ,, The tRNA Phe showed small negative volume changes upon unfolding, the pressure-dependent structural changes being rather small, however, with a maximum of about 15% unpaired bases observed upon pressurization up to 10 kbar . Pioneered by Sugimoto, Chalikian, Macgregor, and their co-workers, it was found that noncanonical nucleic acid structure, including DNA hairpins (DNA-HPs), G-quadruplexes (G4Qs), and i-motifs, are pretty pressure-sensitive, and their pressure-sensitivity varies with their base sequence and the type and concentration of the counterions present in solution. …”
mentioning
confidence: 99%
“…Organisms living under extreme conditions accumulate protein-stabilizing organic cosolvents (also referred to as compatible cosolutes or osmolytes) in their cells, such as glycerol, sorbitol, glycine betaine, or the deep-sea osmolyte trimethylamine- N -oxide (TMAO). ,,, In addition to genetically based adaptations of the structural stability of proteins via mutations of amino-acids (denoted as intrinsic adaptations), extrinsic adaptations using such particular cosolvents are required to achieve the required adaptive changes in the stability and hence function of the proteins. ,,, Remarkably, a given organic osmolyte often shows similar effects on proteins, nucleic acids, and membranes, suggesting common stabilization effects . Similar to the compatible osmoytes, macromolecular crowding has been found to increase the temperature- and in particular the pressure-stability of proteins. ,, The addition of 30 wt % of the macromolecular crowding agent Ficoll (mimicking cell-like crowding conditions) on the ( p – T )-stability diagram of SNase increases the pressure stability by more than 1 kbar at ambient temperatures . Quite expectedly, cosolvents and crowding agents affect not only the structure and stability but also the conformational and internal dynamics of proteins and thus their response to high pressure .…”
mentioning
confidence: 99%
See 3 more Smart Citations